Primers for low‐copy nuclear genes in the Hawaiian endemic Clermontia (Campanulaceae) and cross‐amplification in Lobelioideae1. (16th May 2013) - Pillon, Yohan; Johansen, Jennifer; Sakishima, Tomoko; Chamala, Srikar; Barbazuk, W. Brad; Stacy, Elizabeth A.
Abstract : Premise of the study: Primers were developed to amplify 12 intron‐less, low‐copy nuclear genes in the Hawaiian genus Clermontia (Campanulaceae), a suspected tetraploid. Methods and Results: Data from a pooled 454 titanium run of the partial transcriptomes of seven Clermontia species were used to identify the loci of interest. Most loci were amplified and sequenced directly with success in a representative selection of lobeliads even though several of these loci turned out to be duplicated. Levels of variation were comparable to those observed in commonly used plastid and ribosomal markers. Conclusions: We found evidence of a genome duplication that likely predates the diversification of the Hawaiian lobeliads. Some genes nevertheless appear to be single‐copy and should be useful for phylogenetic studies of Clermontia or the entire Lobelioideae subfamily.